Sustainable Reverse Osmosis application for wastewater treatment in the steel industry. (1st September 2016) - Colla, Valentina; Branca, Teresa Annunziata; Rosito, Felice; Lucca, Carmelo; Vivas, Beatriz Padilla; Delmiro, Vanesa Menéndez
Abstract: The research work presented in this paper is related to water reuse and facility management concepts for the main circuits in different steel plants through the salt elimination techniques. In particular the study concerned two water circuits belonging to two integrated steelworks where high salts concentrations caused relevant problems. In the first circuit, the high chloride and carbonate concentration in the cooling water of the hot strip mill can affect the quality of the strips, due to the salt depositions on the strip surfaces, and causes corrosion of equipment. In the second circuit, the high content of chlorides and fluorides in the process waters of a Blast Furnace gas cleaning system causes corrosion of various components. In both cases tests were carried out to assess the possibility to apply Reverse Osmosis implementation and to evaluate the stability of its qualitative performance to the brackish water. The tests showed that pre-treatments are actually needed for colloids removal, and, consequently, to protect Reverse Osmosis membranes: in the first circuit, ultrafiltration, and in the second circuit conventional coagulation-flocculation-sedimentation system followed by sand filtration have been implemented. Results showed that, through Reverse Osmosis system, most salts, such as chlorides, fluorides, calcium, sulphates, etc. can be removed and other parameters, such as electrical conductivity, alkalinity and Total Dissolved Solids dramatically decreased. Accordingly significant results have been achieved, such as fresh water consumption and water discharged decrease, and the pipe service life improvement, due to the reduction of corrosion problems. The economic viability at industrial scale was also evaluated and their implementation resulted feasible. Highlights: Two water circuits in two integrated steelworks have been considered. The investigation of salt elimination and water reuse has been carried out. The effectiveness of techniques for salts removal have been investigated. The economic and technical feasibilities of the RO integration have been assessed.